GRIYA YATIM PUTERI BANJARBARU - Ihsanul Hakim; Muhammad Deddy Huzairin (ULM Press, 2021)
Griya Yatim Puteri banjarbaru is a dormitory branch of Griya Yatim and Dhuafa Mentaos Banjarbaru as a home for orphaned girls with all their activities with foster parents and located in Banjarbaru City. With the architectural problem, how is the design of Griya Yatim Putri Banjarbaru which is to become a child-friendly residence